The Implementation of TOEIC Preparation to Improve TOEIC Scores of Semester VI at Polytechnic Alkon Kalimantan - Muhammad Rochman; Suzanna Widjajanti (UIBU, 2025)
TOEIC is one of the tests that is used in many universities and according to the director's decree at the Alkon Kalimantan polytechnic campus, the graduation requirements for students who will take the final exam and oral defense must obtain a minimum score of 500. The institution that conducts the test independently is International Testing The program or ITP appointed as the program supervisor for testing on our campus. To make graduates exceed the minimum standard competency score, we hold preparation classes. We held it for a month with a total of 12 meetings. With this minimum standard for graduation, it is hoped that it can become a benchmark so that graduates are expected to have adequate English language skills. By holding preparation classes, it is hoped that when facing tests held by other institutions or official institutions that is appointed, all graduates will be able to exceed a score above 500. This study used qualitative method in which to find out students' preparation when taking the TOEIC test using books and audio that are available and sold in the bookstore market, to find out whether with this preparation their scores can increase as expected. The results of the research show that the scores of students who will be graduating have increased drastically compared to the previous year, where in the previous year there were several students who failed and after this activity was held, the number of students failing to achieve a minimum score of 500 could be reduced.